2015
DOI: 10.1016/j.toxlet.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 receptor antagonist attenuates neonatal lipopolysaccharide-induced long-lasting learning impairment and hippocampal injury in adult rats

Abstract: We have previously reported that neonatal lipopolysaccharide (LPS) exposure resulted in an increase in interleukin-1β (IL-1β) content, injury to the hippocampus, and cognitive deficits in juvenile male and female rats, as well as female adult rats. The present study aimed to determine whether an antiinflammatory cytokine, interleukin-1 receptor antagonist (IL-1ra), protects against the neonatal LPS exposure-induced inflammatory responses, hippocampal injury, and long-lasting learning deficits in adult rats. LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…Here, HT did not have any effect on the key molecules of the IL-1 signaling system we tested, suggesting that IL-1 blockade combined with HT might have additive or synergistic protective effects on both core and penumbra injuries of NE. This is supported by recent preclinical studies from our lab and others demonstrating that the upregulation of IL-1 is involved in the neuroinflammatory processes at play in perinatal brain injury, and that IL-1Ra has a neuroprotective effect against LPS and/or HI-induced brain lesions and subsequent neuro-disabilities (Girard et al, 2012;Lan et al, 2015;Pang et al, 2015;Quiniou et al, 2008;Savard et al, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…Here, HT did not have any effect on the key molecules of the IL-1 signaling system we tested, suggesting that IL-1 blockade combined with HT might have additive or synergistic protective effects on both core and penumbra injuries of NE. This is supported by recent preclinical studies from our lab and others demonstrating that the upregulation of IL-1 is involved in the neuroinflammatory processes at play in perinatal brain injury, and that IL-1Ra has a neuroprotective effect against LPS and/or HI-induced brain lesions and subsequent neuro-disabilities (Girard et al, 2012;Lan et al, 2015;Pang et al, 2015;Quiniou et al, 2008;Savard et al, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…A similar pattern of injury is observed in the encephalopathy of prematurity, with marked neuronal/axonal lesions, astrogliosis, microgliosis, hypomyelination, cerebral volume reduction, and ventriculomegaly [3,8,12]. Moreover, LPS-inflammatory responses in rat pups have been shown to induce long-lasting learning, memory and motor deficits [10,11,13] making this model of inflammatory brain injury clinically relevant to the neurodevelopmental difficulties seen in preterm infants.…”
Section: Introductionmentioning
confidence: 68%
“…. ), bilateral ventricle dilatation and volume reduction of some cerebral structures [6][7][8][9][10][11]. Since oligodendrocyte precursors are very vulnerable to inflammation at these stages of brain development, myelination deficit is also characteristic of this inflammatory injury [6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…IL-1Ra is an endogenous peptide with anti-inflammatory effects that acts as a competitive inhibitor of IL-1 signaling because it antagonizes the IL-1 receptor, expressed at low levels in the membrane of nearly all cell types (67,68). Previous studies have shown that intracerebral IL-1Ra treatment not only blocks IL-1b signaling but can also reduce IL-1b expression levels in the brain (69,70). Clausen et al (71) demonstrated, in a mice model of stroke, that IL-1b and IL-1Ra could be released by different types of microglial cells.…”
Section: Discussionmentioning
confidence: 99%